INTERIOR GATEWAY PROTOCOL ROUTING PERFORMANCE COMPARISON OF THE VIRTUAL PRIVATE NETWORK BASED ON MULTI PROTOCOL LABEL SWITCHING AND DIRECT-LINK BACKUPSED ON MPLS AND DIRECT-LINK BACKUP - Ida Nurhaida; Dimas Widya Putra Pratama; Remmy A. M. Zen; Hong Wei (Universitas Mercu Buana, 2020)
The stability and convergence time become an essential factor in network availability performance. Multiprotocol Label Switching (MPLS) is one of the Virtual Private Network (VPN) technologies that can support the quality of communication media on the high-speed backbone network. Therefore, it is necessary to determine the proper protocol routing in espousing VPN technology based on MPLS supported by direct-link backup to improve network availability in the Data Center. The purpose of this study is comparing the convergence time and Quality of Service (QoS) among the three IGP protocols routing, namely Routing Information Protocol version 2 (RIP), Open Shortest Path First (OSPF), and Enhanced Interior Gateway Routing Protocol (EIGRP) based on two autonomous system number using Ring topology design between Data Center and DRC. Network scenario is created using the Graphic Network Simulator (GNS3) application to measure convergence time and QoS parameters of the three protocols routing and the use of MPLS-TE and RR in enhancing MPLS backbone performance. The results revealed that QoS in the three protocols routing has a good quality level according to TIPHON’s standard with the number of indexes up to 3.25 (Good). On the other hand, the fastest convergence time when interruption on the main link (VPN) is EIGRP with convergence time for about 15 seconds.